Trajectories and predictors of alcohol consumption over 21 years of mothers' reproductive life course - Tran, N.; Williams, G.; Alati, Rosa; Najman, J. (2015)
© 2015 The Authors. Introduction: Little is known about the patterns of women[U+05F3]s alcohol consumption over their reproductive life course. This study identifies trajectories of alcohol consumption by mothers over 21 years of their reproductive life course and examines baseline predictors of these trajectories. Methods: Data were obtained from a prospective cohort study of 3715 women in Brisbane, Queensland, Australia over 21 years of follow-up. Women[U+05F3]s alcohol consumption was measured by frequency and quantity of use across the surveys. Potential predictors and confounding variables were assessed at baseline. Group based-trajectory modelling was used to identify typical drinking trajectories over the maternal reproductive life course. Multinomial logistic regression was employed to examine predictors associated with these trajectories. Results: Four trajectories of alcohol consumption were indentified for mothers over the 21-year period. These trajectories included abstainers (11.9%), low-stable drinkers (58.0%), moderate-escalating drinkers (25.3%), and heavy-escalating drinkers (4.8%). After adjustment for significant covariates, membership of the abstaining trajectory was predicted by lower family income, being married, and high frequency of church attendance while membership of the heavier-escalating trajectory was associated with women who were not currently married, never went church and had unhealthy lifestyle behaviours. Conclusions: Patterns of women[U+05F3]s alcohol consumption exhibit a high level of stability for abstainers and women who drink at low levels. After the birth of their child, there are some changes in alcohol consumption for the moderate and heavy-escalating alcohol consumption groups. Low risk patterns of consumption are associated with variables which generally reflected a low risk behaviour lifestyle. Intervention programmes should particularly target women engaging in the heavy-escalating alcohol consumption group as this group increase their consumption shortly after the birth of their child. There is a need to understand more about the social and health consequences to mothers and their children of being in the moderate and heavy-escalating drinking trajectory groups.